"Stand by the Union, Mr. Arch": The Toronto Labour Establishment and the Emigration Mission of Britain's National Agricultural Labourers' Union - Goutor, David (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2005)
Abstract In the fall of 1873 Joseph Arch, the President of the England’s National Agricultural Labourers’ Union (NALU), embarked on a mission to scout Canada as an emigration destination. He was received with much hospitality in Canada. Large-scale migration of British farm-workers had the support of an extraordinary consensus between the NALU, Canadian political and business élites, and the Toronto labour leaders who wielded enormous influence over the labour movement in Ontario. The consensus was the result of developments in British agricultural unionism, Ontario’s farming sector, Canada’s immigration policy, and the Toronto labour establishment’s approach to immigration. However, during the mission, tensions emerged between Arch and the Toronto labour establishment that strained the appearance of international union solidarity. These tensions revealed the treacherous nature of a relationship between labour leaders in an immigrant-receiving country, and an organization, even a union, looking to promote emigration.